Sorption Uptake of the Molecular Mobility of -Paraffins in ZSM-5 Type Zeolite - M. Bülow; H. Schlodder; P. Struve (Adsorption Science & Technology, 1986)
Sorption uptake of propane and n -hexane on ZSM-5 type zeolite monocrystals has been investigated at 313 K and 323 K, respectively, by means of a constant-volume/variable-pressure method. In the case of propane no reliable information on the molecular mobility could be found. The intracrystalline diffusivity of n -hexane in the Na,H-ZSM-5 zeolite sample is 10 −8 to 10 −9 cm 2 s −1 .